LANGUAGE FUNCTION AND CHOICE IN CLASSROOM LANGUAGE USED BY EFL TEACHER IN SMP NEGERI 2 GIANYAR - Kadek Yunita Dewi; Luh Putu Artini; Luh Gede Eka Wahyuni (Universitas Pendidikan Ganesha, 2022)
This study aimed to describe an analysis of language function and choice toward classroom language used by the EFL teacher in SMP Negeri 2 Gianyar. This study is descriptive qualitative research. The subject of this study is one EFL teacher, and the object of this study is classroom language implemented by one of the English teachers in SMP Negeri 2 Gianyar during distance learning. This study used one instrument with a checklist table and Chamot and O’Malley’s theory about academic language function to answer the research question. The study’s conclusion was used as guidance of the prospective teacher and EFL teacher to improve them in using many kinds of language functions during the learning process. The result showed that the EFL teacher in SMP Negeri 2 Gianyar often used five language functions: seeking information, explaining or informing, persuading, solving the problem, and greeting.